Attitudes of Consumers from the Sarajevo Canton in Bosnia and Herzegovina toward Advertising through Sport among the Question how often Consumers purchase Sporting Goods - Gorica Zoric; Jovan Gardasevic; Izet Bajramovic (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2018)
Unlike other advertising mediums such as TV commercials or online advertising, people involuntarily receive sport advertisements; they prefer to watch the game for the sporting action than the regular advertisements. However, it is important to analyse their general attitudes among various questions, mostly due to the reason it varies from demographic group to demographic group. Hence, this research was aimed at gaining relevant knowledge about the attitudes of Sarajevo consumers toward advertising through sport among the question how often consumers purchase sporting goods. The sample included 358 respondents, divided into six subsample groups: consumers who do not purchase sport goods at all, then consumers who purchase sport goods less than ones a month, next 1-3 a month, 4-6 a month, 7-9 a month, as well as consumers who purchase sport goods more than 10 times a month. The sample of variables contained the system of three general attitudes which were modelled by seven-point Likert scale. The results of the measuring were analysed by multivariate analysis (MANOVA) and univariate analysis (ANOVA) and Post Hoc test.Based on the statistical analyses it was found that significant differences occur at multivariate level, as well as between all three variables at a significance level of (p=.000).